Encyonema oblonga (Bacillariophyta, Cymbellaceae), a new species from Shanxi Province, China - Liu, Qi; Li, Jiajia; Wang, Quanxi; Kociolek, John Patrick; Xie, Shulian (Phytotaxa, 2021)
A new species, Encyonema oblonga Liu & Xie, is collected during a survey of the freshwater diatom flora of Manghe River, Shanxi, China. The valves of this new species are oblong with rounded apices and have the features typical of Encyonema, including complex areolae. We compare the new species with the most similar taxa, E. leei, E. leei var. sinensis and E. appalachianum and consider that  E. leei var. sinensis is the valid name.  The morphology of E. oblonga is documented with light and scanning electron microscopy.